2019
DOI: 10.18502/acta.v57i1.1752
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Irisin Levels and Some Trace Element as a Potential Mark Diagnosis of Gestational Diabetes Mellitus

Abstract: Abstract- The objective of this project was investigating and comparing changes of serum irisin, and trace levels of the elements (Zn, Cu, Mg) in pregnant women with gestational diabetes mellitus GDM in addition to wholesome pregnant group, examining the correlation among (Zn, Cu, Mg) levels and irisin insulin impedance in GDM pregnant women. Sixty GDM pregnant women and thirty wholesome pregnant women were examined. The pair groups were matched for age, and maternal serum irisin. Insulin levels and gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
2
11
1
1
Order By: Relevance
“…AL-Ghazali et al [ 128 ] also confirmed that serum irisin levels in pregnant women with GDM are significantly lower compared to healthy pregnant women. These results, according to the authors of the study, may suggest compensation for the physiological increase in insulin resistance or a stimulatory effect of high estrogen concentrations [ 128 ].…”
Section: Biomoleculesmentioning
confidence: 90%
See 1 more Smart Citation
“…AL-Ghazali et al [ 128 ] also confirmed that serum irisin levels in pregnant women with GDM are significantly lower compared to healthy pregnant women. These results, according to the authors of the study, may suggest compensation for the physiological increase in insulin resistance or a stimulatory effect of high estrogen concentrations [ 128 ].…”
Section: Biomoleculesmentioning
confidence: 90%
“…AL-Ghazali et al [ 128 ] also confirmed that serum irisin levels in pregnant women with GDM are significantly lower compared to healthy pregnant women. These results, according to the authors of the study, may suggest compensation for the physiological increase in insulin resistance or a stimulatory effect of high estrogen concentrations [ 128 ]. It also takes into account possibly its additional secretion by the placenta, although the effect of placental tissue on circulating irisin appears to be insignificant [ 129 ].…”
Section: Biomoleculesmentioning
confidence: 90%
“…Biochemical variables were evaluated in our study in response to the correlation between these and AFM, and we discovered that serum AFM level was significantly positively related to insulin levels, fasting glucose levels, and HOMA-IR values. Although there was no direct evidence supporting our above finding, other GDM studies confirmed that significantly higher levels of fasting blood glucose, fasting insulin, and HOMA-IR were revealed in pregnant women with GDM than that in controls [ 25 ]. Akbas et al also demonstrated that these three biomarkers were increased in GDM patients compared to the controls, and serum cortistatin related to GDM was negatively correlated with these biomarkers [ 21 ].…”
Section: Discussionmentioning
confidence: 43%
“…KA0831, Bio-Techne China Co. Ltd. Shanghai, China) and a human Insulin Quantikine Enzyme-linked immunosorbent assay (ELISA) kit (DINS00, Bio-Techne China Co. Ltd. Shanghai, China). Homeostatic model assessment of insulin resistance (HOMA-IR) was calculated using the following formula: fasting glucose (mmol/L) × fasting insulin (IU/mL)/22.5 [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…En las mujeres embarazadas, la irisina se secreta tambien en la placenta y su concentración aumenta durante la gestación. Los estudios en mujeres con DM gestacional son escasos y con datos controversiales, pero se ha señalado que la irisina se encuentra disminuida en comparación con las mujeres embarazadas sanas y se ha propuesto como marcador para la DM gestacional 35 .…”
Section: Irisinaunclassified